2018
DOI: 10.1166/jnn.2018.14859
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Mesoporous Yolk-Shell Magnetic Prussian Blue Particles for Multi-Functional Nanomedicine

Abstract: Mesoporous magnetic Prussian Blue (PB) particles are good condidates for theragnostic nanomedicine. However, there are lack of efficient methods for fabrication of such materials. Here, we reported the synthesis of the mesoporous yolk-shell Fe3O4@PB particles by one-pot coordination replication and etching. Time-dependent transmission electron microscopy illustrated that the PB crystals nucleated and grew on the surface of Fe3O4 spheres by coordination replication with the help of protons. The extra protons in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…16 A large number of studies have shown that Prussian blue nanoparticles have some important characteristics in the biological environment, such as stability in human serum and efficient cell uptake. [17][18][19][20][21][22] More importantly, PB nanoparticles are a typical US FDA-approved drug in the clinic for treatment of radioactive exposure, demonstrating absolutely approved biosafety in the human body based on sufficient clinical trials. Hollow Prussian nanoparticles have attracted much attention due to their potential to encapsulate large quantities of guest molecules within their empty core domain.…”
Section: Introductionmentioning
confidence: 99%
“…16 A large number of studies have shown that Prussian blue nanoparticles have some important characteristics in the biological environment, such as stability in human serum and efficient cell uptake. [17][18][19][20][21][22] More importantly, PB nanoparticles are a typical US FDA-approved drug in the clinic for treatment of radioactive exposure, demonstrating absolutely approved biosafety in the human body based on sufficient clinical trials. Hollow Prussian nanoparticles have attracted much attention due to their potential to encapsulate large quantities of guest molecules within their empty core domain.…”
Section: Introductionmentioning
confidence: 99%